Pendelmobilität und Familiengründung : Zum Zusammenhang von berufsbedingtem Pendeln und dem Übergang zum ersten Kind - Skora, Thomas (Beiträge zur Bevölkerungswissenschaft, 2018)
Studies show that assuming the role of parents - especially for women - is difficult to reconcile with long commutes. However, the directions of action are still unclear. Does starting a family reduce the willingness to commute longer and are professional disadvantages accepted for this? Or does commuting lead to the postponement of starting a family or even prevent it? With these research questions, the book sheds light on a new explanatory approach for lower employment opportunities in mothers and makes a contribution to the identification of determinants of fertility.